The Influence of Financial Performance on Share Prices in Telecommunications Sub-Sector Companies Listed on BEI - Ubai Dillah; Alwi; Puji Muniarty (Pustaka Digital Indonesia, 2024)
The aim of this research is to determine the effect of financial performance as measured by the Current Ratio, Debt to Equity Ratio, Return On Assets and Price Earning Ratio on share prices in telecommunications companies on the Indonesia Stock Exchange. Sampling method used a purposive sampling method from eighteen companies listed on the Indonesia Stock Exchange in 2018-2022, only three companies were used in the research sample. The data analysis method uses multiple linear regression analysis. Simultaneous test results obtained a calculated F value of 5.823 which is greater than the F Table value with a value of 3.478 (5.823 > 3.478) with a significant value of 0.011 which is smaller than the alpha (ɑ) value of 0.05 (0.011 < 0.05 ). simultaneously PER, DER, ROA, and CR have a significant effect on stock prices. The partial test results show that the four variables used in the research model have a significant influence on stock prices, namely the Return On Asset variable. This is indicated by the significance value produced by this variable being smaller than the α = 5% level. This indicates that this variable has a dominant influence on stock prices .